Why Things go Wrong in the Performance Appraisal System - An Analysis - Hulkund, Vidya L. (Indian Journal of Finance, 2011)
Performance appraisal is the systematic, periodic and an impartial rating of an employee’s excellence in matters pertaining to his present job and his potential for a better job . Performance appraisal is - often a combination of both written and oral elements - in the organization, whereby, the management evaluates and provides feedback on employee job performance. Documenting performance provides a basis for pay increases and promotion. It is the process of obtaining, analyzing and recording information about the relative worth of an employee. Performance appraisal focuses on the performance and future potential of the employee. Modeling S&P CNX Nifty Index Volatility with GARCH Class Volatility Models: Empirical Evidence from India.